THE LEGITIMACY OF THE CALIPHATE AS A STATE SYSTEM - Akbar, Irwan Ahmad; Lilawati, Emi; Rohmah, Hidayatur (Al-Iqro', 2025)
Certain groups believe the Qur'an legitimizes the establishment of a state based on the khilafah system, specifically citing Surah Al-Baqarah (2:30). The purpose of this research is to critically examine the term khalifah in Q. (2:30) using semantic and semiotic approaches. Additionally, the study will explore the historical features of the term in-depth to answer questions regarding the moral ideal conveyed in the verses on khalifah. Specifically, it investigates whether these verses serve as a legal basis for the khilafah system. Furthermore, the researcher will analyze Qur'anic verses and hadiths related to themes of national defense and love for one’s homeland. The study concludes that the assumption that the Qur'an legitimizes the khilafah system is a misconception. Nowhere in the Qur'an does the term khilafah appear; instead, the term used is khalifah. Verses that discuss khalifah do not aim to validate the establishment of a political system based on khilafah. Rather, they represent God’s designation of humankind as His stewards, tasked with managing and utilizing the Earth's resources responsibly.  Moreover, the moral ideal conveyed by the verses on khalifah underscores God’s recognition of humanity as the creation endowed with Ahsanu Taqwim (the most excellent form). This highlights the dignity and responsibility bestowed upon humankind in fulfilling their role as stewards of the Earth.